A Jim Crow State of Mind: The Racialization of Space in the McKinney, Texas Pool Party Incident. (July 2021) - Harris Combs, Barbara
Violence against Black bodies is not new, but contemporary discussions of these matters often focus on police or other state-sanctioned violence against male Black bodies. While this is important, it ignores the perils all Black bodies face as they navigate White spaces. In this article, I utilize an analytical framework, which highlights intersectional bodies in order to expose the extent to which a Jim Crow-like mentality about where people belong still persists in U.S. society. I examine the 2015 McKinney, Texas, pool party incident as a case study to demonstrate how gender and the social status of children operated to imperil Black (and Brown) bodies in the social environment of a predominantly White upper middle-class suburban neighborhood. I offer a counternarrative reading of the incident utilizing a framework I term bodies out of place, a critical extension on critical race theory scholarship and the work of Nirmal Puwar (2004). The article makes an important contribution toward understanding White epistemologies of ignorance with respect to the existence and maintenance of continuing racial oppression and White supremacy in society.